Regulation of Nrf2 by phosphorylation: Consequences for biological function and therapeutic implications - Liu, Tian; Lv, Yi-Fei; Zhao, Jing-Long; You, Qi-Dong; Jiang, Zheng-Yu (Free radical biology & medicine, 2021)
The transcription factor nuclear factor erythroid-derived 2-like 2 (NRF2) participates in the activation of the antioxidant cytoprotective pathway and other important physiological processes to maintain cellular homeostasis. The dysregulation of NRF2 activity plays a role in various diseases, such as cardiovascular diseases, neurodegenerative diseases, and cancer. Thus, NRF2 activity is tightly regulated through multiple mechanisms, among which phosphorylation by kinases is critical in the posttranslational regulation of NRF2. For instance, PKC, casein kinase 2, and AMP-activated kinase positively, while GSK-3 negatively regulates NRF2 activity through phosphorylation of different sites. Here, we provide an overview of the phosphorylation regulation pattern of NRF2 and discuss the therapeutic potential of interventions targeting NRF2 phosphorylation. [Display omitted] •Protein kinases phosphorylate Nrf2 to modulate its stability and/or activity.•Phosphorylation regulation of NRF2 bridges NRF2 activity to a series of biological events.•Targeting NRF2 phosphorylation regulation shows therapeutic potential for multiple inflammation-related diseases.